Role of oxidative stress in PKC-delta upregulation and cardioprotection induced by chronic intermittent hypoxia - Kolár, Frantisek; Jezková, Jana; Balková, Patricie; Breh, Jirí; Neckár, Jan; Novák, Frantisek; Nováková, Olga; Tomásová, Helena; Srbová, Martina; Ost'ádal, Bohuslav; Wilhelm, Jirí; Herget, Jan (American journal of physiology. Heart and circulatory physiology, 2007)
The aim was to determine whether increased oxidative stress during the adaptation to chronic intermittent hypoxia (CIH) plays a role in the induction of improved cardiac ischemic tolerance. Adult male Wistar rats were exposed to CIH in a hypobaric chamber (7,000 m, 8 h/day, 5 days/wk, 24-30 exposures). Half of the animals received antioxidant N-acetylcysteine (NAC; 100 mg/kg) daily before the exposure; the remaining rats received saline. Control rats were kept under normoxia and treated in a corresponding manner. One day after the last exposure (and/or NAC injection), anesthetized animals were subject to 20 min of coronary artery occlusion and 3 h of reperfusion for determination of infarct size. In parallel subgroups, biochemical analyses of the left ventricular myocardium were performed. Adaptation to CIH reduced infarct size from 56.7 +/- 4.5% of the area at risk in the normoxic controls to 27.7 +/- 4.9%. NAC treatment decreased the infarct size in the controls to 42.0 +/- 3.4%, but it abolished the protection provided by CIH (to 41.1 +/- 4.9%). CIH decreased the reduced-to-oxidized glutathione ratio and increased the relative amount of PKC isoform-delta in the particulate fraction; NAC prevented these effects. The expression of PKC-epsilon was decreased by CIH and not affected by NAC. Activities of superoxide dismutase, catalase, and glutathione peroxidase were affected by neither CIH nor NAC treatment. It is concluded that oxidative stress associated with CIH plays a role in the development of increased cardiac ischemic tolerance. The infarct size-limiting mechanism of CIH seems to involve the PKC-delta-dependent pathway but apparently not the increased capacity of major antioxidant enzymes.
Keywords: oxidační stres; Male; Ischemic Preconditioning, Myocardial; Rats, Wistar; Up-Regulation; Protein Kinase C-delta; proteinkinasa C-delta; chronická nemoc; Hypoxia; sekundární prevence; upregulace; mužské pohlaví; potkani Wistar; Secondary Prevention; Chronic Disease; infarkt myokardu; krysa rodu Rattus; Animals; zvířata; Myocardial Infarction; Rats; ischemické přivykání; Oxidative Stress; hypoxie